BUSINESS AND LABOR COALITION FOR EMPLOYEE PRIVACY (Tufts Archival Research Center, 2007)
Report describing the business and labor coalition for employee privacy. Outlines purpose of the coalition, rationale for concern about employee privacy, legislation protecting employees from engaging in legal activities off the job, and proposed members to join the coalition.